Social support and coping strategies as predictors of marital interaction in couples experiencing unintended pregnancy - Reviani, Nia; Sumarwan, Ujang; Herawati, Tin; Yuliati, Lilik Noor (Poltekkes Kemenkes Bandung, 2026)
Background: Unintended pregnancy (UP) is a reproductive health problem that can undermine psychological well-being, social functioning, and family dynamics, particularly marital interaction. Objective: This study aimed to analyze the extent to which social support and coping strategies predict the quality of marital interaction among couples experiencing UP. Methods: A cross-sectional design was employed involving 200 couples from Bekasi City and Bekasi Regency, Indonesia, selected using purposive sampling. Data were collected through structured interviews using standardized questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The results showed that most couples reported low levels of social support and marital interaction, while coping strategies were generally at a moderate level. Social support had a significant positive effect on both coping strategies (p < 0.01) and marital interaction (p < 0.01), and coping strategies also had a significant positive effect on marital interaction (p < 0.05). Conclusion: These findings highlight the importance of strengthening social support networks and enhancing adaptive coping skills to improve marital quality and foster family resilience in the context of unintended pregnancy.